Anatomy of the vibration characteristics in old arch dams by random field theory. (15th January 2019) - Hariri-Ardebili, Mohammad Amin; Mahdi Seyed-Kolbadi, S.; Saouma, Victor E.; Salamon, Jerzy W.; Nuss, Larry K.
Highlights: Formulation of random field theory for the elastic properties of old concrete dams. Evaluation of the correlation length effect on the frequency response dispersion and inter-correlation among vibrational modes. First-time analysis of six arch dams in the context of a "dam class". Proposal of an experimental design using a dam frequency analytical model. Proposal of an iterative random field-based system identification technique for arch dams. Abstract: Determining vibration characteristics constitutes the first step in calibrating the finite element model in an old arch dam analysis. These characteristics provide the required information for a proper dynamic analysis of the coupled fluid-structure system used for risk assessment purposes. This paper investigates the detailed vibration characteristics of arch dams with heterogeneous material by applying random field theory. A group of six double-curvature arch dams are studied herein. The spatial material distribution using different correlation lengths is compared, and the response dispersion is quantified. An experimental meta-model design is developed for a specific class of dams, with an approximate analytical solution being derived. Ultimately, an iterative, random field-based system identification technique is proposed for old arch dams.